Metabolomics-based analysis of dynamic metabolic trajectories and regulatory networks in two-stage fermentation of kiwifruit wine - Wangsheng Sun; Pengfei Bi; Wanju Yan; Rou Cai; Zhendong Zhang; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Jing Guo (Food Microbiology, 2027)

High-P-T experimental constraints on the genesis of post-collisional porphyry Cu-Au magmas: A case study from the southeastern Tibetan Plateau - Gong Liu; Xian-Wu Bi; Lei-Luo Xu; Wei Du; Lin-Bo Shang; Jing-Jing Zhu; Ming-Liang Huang; Rui Ma (Lithos, 2026)

Carbon dots-doped light conversion coatings enhance pigment biosynthesis and capsaicinoids accumulation in postharvest peppers (Capsicum annuum L.) - Pengpeng Mao; Hong Xu; Xueting Bi; Bingfu Lei; Wei Li; Rui Li; Yinjian Zheng (Postharvest Biology and Technology, 2026)

Oxidized Late Devonian arc intrusion in the Jiangda area, eastern Tibet: Implication for heterogeneous porphyry Cu-Au fertility of Paleo-Tethyan arc magmas - Rui Ma; Ming-Liang Huang; Lei-Luo Xu; Jing-Jing Zhu; Bao-Di Wang; Hong-Rui Zhang; Rui-Zhong Hu; Xing-Chun Zhang; Xian-Wu Bi (Journal of Asian Earth Sciences, 2026)

Cuminal-triggered mitophagy induces mitochondrial dysfunction, resulting in decreased vegetative growth and pathogenicity in Trichothecium roseum - Rui Kang; Zhong Zhang; Pengfei Sun; Xiaobin Xu; Horchelle T. Djomptchouang; Yang Bi; Dov Prusky; Kumsa Delessa Kuffi (International Journal of Food Microbiology, 2026)

Modulating local structural disorder in layered cathodes with alternating edge- and face-sharing octahedra for enhanced high-rate performance - Chengjun Fan; Xiaoxia Yang; Lingling Yao; Qin Wang; Xiao Ouyang; Leidang Zhou; Zhiwen Gao; Rui Jia; Xibang Chen; Jing Chen; Hao Liu; Bin Liao; et al. (Chemical Engineering Journal, 2026)

Characterization of GSTz2 involved in cyantraniliprole and emamectin benzoate detoxification in Drosophila suzukii - Yongqi Yan; Chongzhi Wang; Mingzhe Li; Shiwei Guo; Xuxing Li; Jingyan Yu; Xiaoqing Fang; Rui Bi (Journal of Asia-Pacific Entomology, 2026)

Tailoring polyhydroxybutyrate by molecular weight regulation: Green synthesis, food-grade performance and innovative ketogenic applications - Jin Hui Xie; Jia Ying Xin; Yan Wang; Li Rui Sun; Hai Xin Bi; Jian Xiong Zhang; Chun Gu Xia (Food Research International, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Predefined-time trajectory tracking control of autonomous underwater vehicle with input saturation and disturbance observer based on improved performance function - Baohe Sun; Lingpeng Ouyang; Yanchao Sun; Yixiang Bi; Rui Feng; Hongde Qin (Ocean Engineering, 2026)

Distinct differences of rice grain quality caused by developmental stage and cultivar: A widely targeted metabolomics perspective - Xuexia Yuan; Pingxiang Liu; Rui Gao; Jingxiu Bi; Tong Zhao; Haining Hao; Xia Li; Yutao Wang (Food Chemistry, 2026)

Origins of Miocene basaltic magmatism in the western Yarlung-Tsangpo Suture Zone, southern Tibet: Insight into the lateral and longitudinal tearing of the subducted Indian continental slab - Jianbo Cheng; Xianshu Dong; Yalin Li; Shuai Li; Siqi Xiao; Wenjun Bi; Rui Zhou (Chemical Geology, 2026)

Identification of Geochemical Anomalies Using a Deep Semi-supervised Anomaly Detection Model - Rui Bi; Di Liu; Qinglin Xia (Natural Resources Research, 2026)

Depth-dependent phosphorus leaching risks in littoral soils of Lake Dianchi under extreme rainfall - Leibo Ding; Wenbin Zhou; Rui Liu; Kaimin Shih; Xingyu Deng; Xiaoyi Bi; Wei Ma (Environmental Geochemistry and Health, 2026)

Low abundance microorganisms enhance soil multifunctionality by emphasizing fungal roles as mediated by plant biomass - Ze-Ying Zhao; Xiao-Bin Xiong; Peng-Yang Wang; Jia-Cheng Guo; Yinglong Chen; Hong-Yan Tao; Nan Chang; Cheng-Rui Bi; Yun-Lu Chen; Yuan Song; You-Cai Xiong (Applied Soil Ecology, 2026)

Spatially explicit process-resolved fluxes and microbial drivers: Linking community succession to greenhouse gas emissions from full-scale industrial wastewater treatment - Weiwei Kong; Rui Dai; Zhaohui Yang; Qinyang Li; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Journal of Water Process Engineering, 2026)

Constructing a Z-scheme heterojunction on leather waste-derived biochar supporting graphitic carbon nitride for highly-efficient photocatalysis toward water decontamination - Liming Zhao; Rui Dai; Yuling Tang; Xin Cheng; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2026)

Algal ecological dynamics tracking model for studying hydrodynamic impacts on algae transport and accumulation in a shallow lake - Fei Du; Xiaobo Liu; Shiyan Wang; Chang Liu; Aiping Huang; Weijie Wang; Budong Li; Rui Gao; Xin Tian; Zhen Han; Hao Fan; Bi Wu (Journal of Hydrology, 2026)

Deciphering the mechanisms underlying cadmium tolerance in the endophytic fungus Trichoderma atroviride D16 - Xue-Wen Bi; Xing-Guang Xie; Wen-Jing Zhang; Rui-Di Zhang; Khalid Rahman; Xin-Zhu Yu; Cun-Yu Fan; Shu-Lang Ding; Yu-Qing Peng; Ting Han (Fungal Biology, 2026)

A coupled strain-damage framework for rock deformation and dynamic damage under cyclic loading based on mesoscale elastoplastic elements - Haohao Zhang; Rui Chen; Yazhou Wang; Huijie Bi; Chaojun Fan; Hui Peng (Computers and Geotechnics, 2026)

Drivers of biogenic secondary organic aerosols in Eastern China: Evidence from machine learning and high-resolution measurements - Kun Zhang; Meng Xiu; Xiaohui Bi; Yanan Yi; Rui Li; Biao Zhou; Ruixin Pan; Hui Chen; Jian Zhen Yu; Li Li (Journal of Hazardous Materials, 2026)

Three new species of Scleroderma from Southern China - Ling Li; Hua Qu; Rong-Qian Bi; Rui Wu; Hai-Jiao Li; Zai-Wei Ge (Mycological Progress, 2026)

Palm oil-based chemically interesterified fat: An alternative to lard regarding application in traditional Chinese táo sū - Linshang Zhang; Yingjing Bi; Rui Zhang; Yueting Niu; Fanfan Song; Shangde Sun (Food Chemistry, 2026)

Joint Characterization and Stability Analysis: Measurement Techniques and Engineering Implications - Rui-yang Bi; Chao-shui Xu; Zu-pu Xuan; Jian Zhou; Kun Du (Rock Mechanics and Rock Engineering, 2026)

Study on pore characteristics of sandstone with different preloading ratios under high temperature - Chaolin Wang; Rui Wu; Can Du; Wei Tang; Jing Bi (Bulletin of Engineering Geology and the Environment, 2026)

Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

Valorization and evaluation of acidic and neutral polysaccharides from Panax ginseng processing residues for the mitigating effects on skin aging - Boyu Xiong; Rui Liu; Xinyi Zhi; Yanru Li; Jiameng Sun; Kaixuan Mao; Lei Yu; Yunfeng Bi (Food Research International, 2025)

Miocene N-MORB- and OIB-type diabase dikes in the western Yarlung Tsangpo suture zone, southern Tibet: Insights into the Indian slab tearing and asthenosphere–lithosphere interaction - Jianbo Cheng; Yalin Li; Xianshu Dong; Siqi Xiao; Shuai Li; Wenjun Bi; Rui Zhou (Lithos, 2025)

Genetic sensitivity moderates the effects of joint exposure to air pollution on depression risk: a genome-wide by environment interaction analysis - Yaoyao Sun; Xue Lv; Wenjian Bi; Yuyanan Zhang; Zhe Lu; Jing Guo; Zhewei Kang; Xiaoyang Feng; Yundan Liao; Guorui Zhao; Junyuan Sun; Yang Yang; et al. (Environmental Pollution, 2025)

Vertical distribution, optical properties, and source attribution of summer dust in southern Tajikistan: ground-based observations and model results - Zhongwei Huang; Qingqing Dong; Tian Zhou; Jianrong Bi; Rui Chen; Qiantao Liu; Sabur F. Abdullaev; Dilovar Nozirov; Khan Alam; Tianhe Wang; Wuren Li; Ze Li; et al. (Atmospheric Environment, 2025)

Rapid recovery of bisphenol A-inhibited anammox biofilm systems by exogenous AHLs addition - Shaopo Wang; Ruimin Tian; Yanmeng Bi; Fansheng Meng; Rui Zhang; Chenchen Wang; Dong Wang; Lingjie Liu; Xiangyu Zhang; Xinpei Guan (Journal of Water Process Engineering, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Revisiting the Indium Window effect: Insights from sphalerite big data - Qi-Nan Zou; Yu-Miao Meng; Rui-Zhong Hu; Xiao-Wen Huang; Xian-Wu Bi; Tai-Ping Zhao (Journal of Asian Earth Sciences, 2025)

Tailoring sponge-like nitrogen-enriched biochar: A green and sustainable remediation technology for Pb and Cu contaminated soil - Jianhua Qu; Rui Yu; Mengning Wang; Nanfang Wang; Fuxuan Bi; Hang Gao; Chang Qin; Yifan Wang; Ying Zhang (Chemical Engineering Journal, 2025)

Telaprevir attenuates caspase-11-dependent pyroptosis in mouse heart following ischemia/reperfusion via inhibition of MALT1/TRAF6 pathway - Ming-Rui Li; Bi-Feng Yao; Can Tang; Xiu-Ju Luo; Jun Peng (Toxicology and Applied Pharmacology, 2025)

Ga- and Ge-bearing minerals and trace element-rich magnetite in the Makeng skarn Fe polymetallic deposit, Eastern China - Xiang-Xue Weng; Yu-Miao Meng; Xiao-Wen Huang; Lin-Bo Shang; Rui-Zhong Hu; Xian-Wu Bi (Journal of Asian Earth Sciences, 2025)

Effect of non-Saccharomyces yeast combinations and lactic acid bacteria inoculation timing on fermentation performance and aroma quality of kiwifruit wine - Wangsheng Sun; Wanju Yan; Rou Cai; Zhendong Zhang; Pengfei Bi; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Fangyu Long; Jing Guo (Food Bioscience, 2025)

Predicting the flavor potential of green coffee beans with machine learning-assisted visible/near-infrared hyperspectral imaging (Vis-NIR HSI): Batch effect removal and few-shot learning framework - Minping Wu; Zhuangwei Shi; Haiyu Zhang; Rui Wang; Jiayi Chu; Shao Quan Liu; Heming Zhang; Hai Bi; Weihua Huang; Rui Zhou; Chenhui Wang (Food Control, 2025)

Failure mechanism of anchored anti-dip rock slope subjected to strong earthquakes: Insights from large-scale shaking table tests - Shanbai Wu; Liangqing Wang; Hans-Balder Havenith; Jianlin Tian; Qiong Wu; Changdong Li; Rui Ke; Chenlu Wang; Xiaochao Bi (Engineering Geology, 2025)

Activation of the circAGFG1/miR-195-5p/PD-L1 axis induces lung injury in sepsis - Yang Bi; Rui Ding; Xinyan Liu; Yun He; Xukun Liu; Shouye Ma; Chaofan Wang; Zhongfa Zhang; Xuan Song (Human Cell, 2025)
Severe sepsis can escalate to acute lung injury (ALI), a critical condition with limited treatment options. Emerging research highlights the role of non-coding RNAs, including microRNAs (miRNAs) and circular RNAs (circRNAs), in regulating epithelial and immune cell responses in sepsis-induced ALI. This study delves into the circAGFG1/miR-195-5p/PD-L1 axis to elucidate its potential in this context. The conducted experiments using Th17 cells differentiated from CD4+ T cells isolated from human umbilical cord blood, co-cultured with transfected Calu-3 cells. The assessed cell viability, RNA, and protein expression levels under inflammatory stimuli. In addition, we collected bronchoalveolar lavage fluid and lung tissues from a cecal ligation and puncture mouse model. Quantification of RNA and protein expression of inflammatory and survival markers provided insights into the regulatory mechanisms involved. Peripheral blood samples from sepsis/ALI patients and healthy controls revealed that circAGFG1 expression is significantly downregulated, while miR-195-5p expression is upregulated in patients compared to healthy individuals. In both Calu-3 cells and induced Th17 cells, as well as in sepsis-induced ALI mouse models, the circAGFG1/miR-195-5p/PD-L1 axis was shown to regulate the expression of inflammatory cytokines, Th17 cell differentiation, and markers of epithelial cell survival. Results show the circAGFG1/miR-195-5p/PD-L1 axis plays a critical role in the pathogenesis of sepsis-induced ALI. Targeting this axis could present a novel therapeutic strategy for preventing ALI in sepsis and other conditions characterized by heightened lung inflammation. This research paves the way for new treatment approaches, offering hope for improved outcomes in patients suffering from severe sepsis and ALI. Graphical abstract

Dispersion stability and thermal conductivity of modified ZnO/HFE-7100 nano-coolant - Yuxin Yang; Rixin Zhang; Rui Liang; Yike Gao; Chenyang Zhang; Junwei Cui; Shengshan Bi (International Journal of Refrigeration, 2025)

Calcium phytate cross-linked polysaccharide hydrogels for selective removal of U(VI) from tailings wastewater - Lan Lei; Rui Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Xin Liu; Tie-Ying Shi; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Water Research, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

The Trp-574-Leu mutations together with enhanced metabolism contribute to cross-resistance to ALS inhibiting herbicides in Fimbristylis littoralis - Yueyue Shi; Zhiwen Wu; Rui Cheng; Lilei Zhang; Xiaoxiao Guo; Xuefeng Li; Yaling Bi (Pesticide Biochemistry and Physiology, 2025)

Atmospheric carbonyls in urban Beijing in the summertime under the continuous implementation of clean air actions: Decreasing trends, source apportionments and new insights for control strategies - Xin Zhang; Fang Bi; Mingzhu Li; Lu Zhao; Hao Zhang; Yunfeng Li; Likun Xue; Rui Gao; Yujie Zhang; Xuezhong Wang; Zhenhai Wu; Zhanshan Wang; et al. (Journal of Cleaner Production, 2025)

New insight into the role of bisphenol A on the anammox system: Oxidative stress and quorum sensing mechanisms - Yu Tian; Lingjie Liu; Chunsheng Qiu; Dong Wang; Rui Zhang; Yanmeng Bi; Shaopo Wang; Bo Zhang (Journal of Environmental Chemical Engineering, 2025)

Microwave-assisted synthesis and functionalization of biochar for environmental remediation: Regulate strategy and application potential - Jianhua Qu; Rui Yu; Xiaoyang Liu; Wei Peng; Fuxuan Bi; Xu Liu; Qiwen An; Yupeng Zhang; Qi Hu; Ying Zhang (Journal of Environmental Chemical Engineering, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

RNA interference-mediated silencing of GNBP2 reduces the immunity of stored pest Tribolium castaneum against bacteria - Jingxiu Bi; Xiangjun Ma; Yuying Jiang; Pingxiang Liu; Rui Gao; Tong Zhao; Xuexia Yuan; Haining Hao; Bin Li; Yutao Wang (Pesticide Biochemistry and Physiology, 2025)

Berbamine inhibits Pseudorabies virus in vitro and in vivo - Liang Li; Muze Lv; Yangfan Li; Huihui Sun; Jie Li; Wenyan Li; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jun Wang; et al. (Veterinary Microbiology, 2025)

An evolutionary optimization-learning hybrid algorithm for energy resource management - Rui Qi; Ya-Hui Jia; Wei-Neng Chen; Ying Bi; Yi Mei (Swarm and Evolutionary Computation, 2025)

Species-specific accumulation of microplastics in different bird species from South China: A comprehensive analysis - Ying Zeng; Junjie Cai; Yujing Zhu; Jichao Wang; Rui Guo; Li Jian; Xiaobo Zheng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

The characteristics of phthalate acid esters and bisphenol A in PM2.5 of a petrochemical city: Concentrations, compositions, and health risk assessment in Dongying - Fangyun Long; Yanqin Ren; Yuanyuan Ji; Xurong Bai; Hong Li; Gehui Wang; Xiaoyu Yan; Yubao Chen; Junling Li; Haijie Zhang; Rui Gao; Fang Bi; et al. (Environmental Pollution, 2025)

Cross‐Continental Shifts of Ecological Strategy in a Global Plant Invader - Ramona E. Irimia; Weihan Zhao; Peipei Cao; Madalin Parepa; Zhi‐Yong Liao; Shengyu Wang; Jeannie M. Mounger; Conner Richardson; Fatima Elkott; Xin Zhuang; Jingwen Bi; Jieren Jin; et al. (Global Ecology and Biogeography, 2025)
Aim Plant invasions are a global problem that requires studying plants and their environmental associations across native and introduced ranges. Location 2000 km transects in China, Europe and North America. Time Period June 2019–July 2020. Major Taxa Studied Japanese knotweed ( Reynoutria japonica ). Methods We surveyed 150 populations of Japanese knotweed, a noxious invader of the temperate zone, along 2000 km transects in native China and the introduced ranges of Europe and North America. Results We found that larger plants and denser populations in the introduced ranges were associated with shifts in leaf economy and chemical defences. Introduced knotweed populations had higher SLA but reduced leaf chlorophyll, lignin, C:N ratio and leaf toughness along with altered leaf tannins, flavonoids and alkaloids. We found three distinct multivariate knotweed phenotypes primarily in the introduced ranges, and two multivariate knotweed phenotypes mainly in native populations. Main Conclusions Decreased herbivore and pathogen impacts in introduced populations and changes in environmental associations indicate that enemy release and novel habitat conditions might have driven the emergence of novel ecological strategies in this global plant invader.

Comparative investigation on the adsorption behavior of bromate in aqueous solutions using Zn/Ni/Al-LDH and Ni/Al-LDH: optimization, equilibrium analysis, and mechanistic insights - Yaping Qin; Huixue Ren; Shengyun Jiang; Yuxin Bi; Chuntong Li; Rui Fang (Journal of Environmental Health Science and Engineering, 2025)

Multi-factor optimization of coaxial borehole heat exchanger based on Taguchi and matrix method - Shimin Wang; Pengtao Wang; Jian'an Wang; Rui Liang; Jie Zhang; Ke Zhang; Jian Liu; Xingchen Lu; Shaoqiang Sui; Shengshan Bi (Geothermics, 2025)

Manganese exposure leads to depressive-like behavior through disruption of the Gln–Glu–GABA metabolic cycle - Yujie Bi; Nannan Huang; Duo Xu; Shenshen Wu; Qingtao Meng; Hanqing Chen; Xiaobo Li; Rui Chen (Journal of Hazardous Materials, 2024)

Effect of yeast (Saccharomyces cerevisiae) fermentation on conformational changes in pig liver proteins and their ability to bind to characteristic aldehydes - Jin Luo; Li Liang; Jingcheng Zhang; Yongzhao Bi; Rui Yang; Baoguo Sun; Yuyu Zhang (Food Chemistry, 2024)

Biogeography of a Global Plant Invader: From the Evolutionary History to Future Distributions - Lei Zhang; Isolde van Riemsdijk; Mu Liu; Zhiyong Liao; Armand Cavé‐Radet; Jingwen Bi; Shengyu Wang; Yujie Zhao; Peipei Cao; Madalin Parepa; Oliver Bossdorf; Armel Salmon; et al. (Global Change Biology, 2024)
Biological invasions pose a global challenge, affecting ecosystems worldwide and human societies. Knowledge of the evolutionary history of invasive species is critical to understanding their current invasion success and projecting their future spread. However, to date, few studies have addressed the evolutionary history and potential future spread of invaders simultaneously. In this study, we explored both evolutionary history and spatiotemporal dynamic patterns of the distribution of Reynoutria japonica , known as one of the world's worst plant invaders. We analysed 265 R. japonica samples from its current geographical ranges across three continents, using seven chloroplast DNA (cpDNA) markers to establish the phylogenetic relationships among extant populations. We combined these with ecological niche modelling to infer historical and more recent migration patterns and predict potential future distribution changes under climate change. Our results indicate that climate fluctuations and sea level changes likely facilitated the expansion of R. japonica from southern Japan to continental East Asia in the Pliocene, followed by a contraction in East Asian populations. In the recent Holocene, human activities have then enabled a linage of this species to spread from Japan to Europe and North America, resulting in three major global clades. Future climate scenarios suggest a northward expansion of R. japonica in Europe and North America, but shrinking habitat in China. Our study, thus, demonstrates the complex influences of historical climate‐driven migrations, human activities and future climate changes on the global distribution of an invasive species.

Berbamine inhibits porcine epidemic diarrhea virus in vitro and in vivo - Hongwei Xiang; Jixue Qiao; Haicheng Lin; Jie Li; Yangfan Li; Huihui Sun; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jinchi Zhou; et al. (Veterinary Microbiology, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Geographic variation in leaf traits and palatability of a native plant invader during domestic expansion - Yu‐Jie Zhao; Shengyu Wang; Zhi‐Yong Liao; Madalin Parepa; Lei Zhang; Peipei Cao; Jingwen Bi; Yaolin Guo; Oliver Bossdorf; Christina L. Richards; Jihua Wu; Bo Li; et al. (Ecology, 2024)
Like alien plant invasion, range expansion of native plants may threaten biodiversity and economies, rendering them native invaders. Variation in abiotic and biotic conditions across a large geographic scale greatly affects variation in traits and interactions with herbivores of native plant invaders, which is an interesting yet mostly unexplored issue. We used a common garden experiment to compare defensive/nutritional traits and palatability to generalist herbivores of 20 native (23.64° N–30.18° N) and introduced range (31.58° N–36.87° N) populations of Reynoutria japonica , which is a native invader following range expansion in China. We analyzed the relationships among herbivore pressure, climate, plant chloroplast haplotypes, leaf traits, and herbivore performance. Of the 16 variables tested, we observed range differences in 11 variables and latitudinal clines in nine variables. In general, herbivores performed better on the introduced plants than on the native plants, and better on the high‐latitude plants than on the low‐latitude plants within the introduced populations. Three key traits (leaf thickness, specific leaf area, and carbon‐to‐nitrogen [C:N] ratio) determined palatability to herbivores and were significantly associated with temperature and/or precipitation of plant provenance as well as with plant haplotypes but not with herbivore pressure. Our results revealed a causal sequence from plant‐range‐based environmental forces and genetic context to plant quality and palatability to herbivores in R. japonica . These findings suggest a post‐introduction evolution of R. japonica , which may partly explain the colonization success of this important native, but invasive plant.

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

Dexmedetomidine attenuates ferroptosis by Keap1-Nrf2/HO-1 pathway in LPS-induced acute kidney injury - Rui-Rui Luo; Jing Yang; Yan-Lin Sun; Bi-Ying Zhou; Si-Xuan Zhou; Guo-Xing Zhang; Ai-Xiang Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Hybrid neural network wind speed prediction based on two-level decomposition and weighted averaging - Qi Bi; Yu-long Bai; Zai-hong Hou; Rui Wang (Earth Science Informatics, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

HT-2 toxin impairs porcine oocyte in vitro maturation through disruption of endomembrane system - Jia-Rui Li; Si-Le Wu; Lin-Lin Hu; Bi-Yun Liao; Shao-Chen Sun (Theriogenology, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Duplex Real-Time Fluorescent Quantitative PCR Assays for the Detection of Toxigenic Microcystis Genotypes Based on SNP/InDel Variation in mcy Gene Cluster - Xiangdong Bi; Peng Wei; Qian Wang; Lijin Duan; Wei Dai; Rui Chen; Dajuan Zhang (Current Microbiology, 2024)

Enhanced photocatalytic U(VI) reduction via double internal electric field in CoWO4/covalent organic frameworks p-n heterojunction - Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Xiao-Xing Wang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

The transport of bismuth in HCl-bearing aqueous vapour and low-density aqueous supercritical fluids: Implications for natural systems - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Qi Liu; Fei-Xiang Liu; Yuan Mei; Zi-Qi Jiang; Lin-Bo Shang; Jing-Jing Zhu; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2024)

A review of distribution and functions of extracellular DNA in the environment and wastewater treatment systems - Shaopo Wang; Ruimin Tian; Yanmeng Bi; Fansheng Meng; Rui Zhang; Chenchen Wang; Dong Wang; Lingjie Liu; Bo Zhang (Chemosphere, 2024)

Effect of volatile compounds produced by Weissella cibaria BWL4 on Botrytis cinerea infection in fruit and complete genome sequence analysis of BWL4 - Danfeng Zhang; Xuehua Xu; Xinrui Tian; Rui Wang; Tingting Hu; Wei Shi; Wanling Bi; Yingwang Ye (Postharvest Biology and Technology, 2024)

Victoria amazonica-inspired sandwich-structure interfacial solar steam generator - Junjie Pan; Xin Zhang; Chenglong Zhang; Wenfeng Hu; Siyi Bi; Huiqi Shao; Nanliang Chen; Rui Yu; Jinhua Jiang; Guangwei Shao (Chemical Engineering Journal, 2024)

Discovery of the tigecycline resistance gene cluster tmexCD3-toprJ1 in Pasteurella multocida strains isolated from pigs in China - Congcong Shi; Zhanwei Zhu; Yuyao Shang; Wenbo Song; Jie Yang; Haixin Bi; Zihao Wang; Rui Xie; Mengfei Zhao; Lin Hua; Huanchun Chen; Bin Wu; et al. (Veterinary Microbiology, 2024)

Development of an analytic method for organosulfur compounds in Welsh onion and its use for nutritional quality analysis of five typical varieties in China - Pingxiang Liu; Peng Wu; Jingxiu Bi; Yuying Jiang; Rui Gao; Lei Gao; Yonghua Li; Tong Zhao; Xiao Zhang; Chao Zhang; Yutao Wang (Food Chemistry, 2024)

Oxygen-enriched vacancy spinel Mn-Co oxides by deep thermal reduction for enhanced antibiotics degradation efficiency - Xiai Zhang; Rui Zhou; Ruohong Bi; Tong Wang; Qikui Fan; Hao Zhu; Zhimao Yang; Xiaofei Liu; Chuncai Kong (Journal of Environmental Chemical Engineering, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Core-shell MOF@COF photocatalysts for synergistic enhanced U(VI) and tetracycline cleanup through space and carrier separation - Rui-Xiang Bi; Xin Liu; Lan Lei; Zhi-Hai Peng; Xiao-Xing Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Detection and analysis of landslide geomorphology based on UAV vertical photogrammetry - Rui Bi; Shu Gan; Xiping Yuan; Kun Li; Raobo Li; Weidong Luo; Cheng Chen; Sha Gao; Lin Hu; Zhifu Zhu (Journal of Mountain Science, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

3D reconstruction and characterization of cotton bolls in situ based on UAV technology - Shunfu Xiao; Shuaipeng Fei; Yulu Ye; Demin Xu; Ziwen Xie; Kaiyi Bi; Yan Guo; Baoguo Li; Rui Zhang; Yuntao Ma (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Shale reservoir storage of hydrogen: Adsorption and diffusion on shale - Chaolin Wang; Yu Zhao; Rui Wu; Jing Bi; Kunpeng Zhang (Fuel, 2024)

Synergistic effect triggered by Fe2O3 and oxygen-induced hydroxyl radical enhances formation of amino-phenolic humic-like substance - Yingchao Zhang; Zhitao Bi; Wenxin Tian; Zhenyu Ge; Yang Xu; Rui Xu; Hongqiong Zhang; Shoufeng Tang (Journal of Environmental Management, 2023)

Chemical constituents from Vitex negundo var. cannabifolia (Sieb. et Zucc.) Hand.-Mazz. (Lamiaceae) and their chemotaxonomic significance - Muhammad Aurang Zeb; Peng-Yun Yang; De-Wen Bi; Wen-Chao Tu; Xiao-Li Li; Rui-Han Zhang; Xing-Jie Zhang; Wei-Lie Xiao (Biochemical Systematics and Ecology, 2023)

The predictive, preventive, and personalized medicine of insomnia: gut microbiota and inflammation - Hao-Wen Chen; Rui Zhou; Bi-Fei Cao; Kuan Liu; Qi Zhong; Yi-Ning Huang; Hua-Min Liu; Jin-Qing Zhao; Xian-Bo Wu (EPMA Journal, 2023)

The impact of freezing methods on the quality, moisture distribution, microstructure, and flavor profile of hand-grabbed mutton during long-term frozen storage - Yulong Luo; Yongzhao Bi; Rui Du; Hong Yuan; Yanru Hou; Ruiming Luo (Food Research International, 2023)

Significantly improved high-temperature capacitive performance in polymer dielectrics utilizing ultra-small carbon quantum dots with Coulomb-blockade effect - Hangchuan Cai; Rui Wang; Bin Gou; Jing Fu; Yujie Zhu; Hao Yang; Jiangang Zhou; Manxi Li; An Zhong; Daoming Zhang; Huasong Xu; Chunhui Bi; et al. (Chemical Engineering Journal, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Biotrophic interactions between plant and endophytic bacteria in removal of PAHs and Cd from contaminated soils enhanced by graphene oxide - Lingmei Li; Rui Liu; Jianjun Chen; Peidong Tai; Xiaoyi Bi; Ping Zou; Yajie Wang; Yao Xiao (Journal of Cleaner Production, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

F-box and leucine-rich repeat protein 16 controls tamoxifen sensitivity via regulation of mitochondrial respiration in estrogen receptor-positive breast cancer cells - Feng Chen; Lu Wang; Yanrong Feng; Wenxin Ma; Junqin Liu; Qianyao Bi; Yao Song; Rui Gao; Yanhan Jia (Human Cell, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

High-throughput calculation of organ-scale traits with reconstructed accurate 3D canopy structures using a UAV RGB camera with an advanced cross-circling oblique route - Shunfu Xiao; Yulu Ye; Shuaipeng Fei; Haochong Chen; Bingyu zhang; Qing li; Zhibo Cai; Yingpu Che; Qing Wang; AbuZar Ghafoor; Kaiyi Bi; Ke Shao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Seasonal associations between air pollutants and influenza in 10 cities of southern China - Rui Zhang; Yonghong Li; Peng Bi; Siyuan Wu; Zhibin Peng; Yujie Meng; Yu Wang; Songwang Wang; Yushu Huang; Juan Liang; Jing Wu (International Journal of Hygiene and Environmental Health, 2023)

Genetic and Phenotypic Spectrum of Amyotrophic Lateral Sclerosis Patients with CCNF Variants from a Large Chinese Cohort - Bi Zhao; Qirui Jiang; Junyu Lin; Qianqian Wei; Chunyu Li; Yanbing Hou; Bei Cao; Lingyu Zhang; Ruwei Ou; Kuncheng Liu; Tianmi Yang; Yi Xiao; et al. (Molecular Neurobiology, 2023)
Cyclin F (CCNF) variants have been found to be associated with amyotrophic lateral sclerosis (ALS)/frontotemporal dementia (FTD). However, the genetic and clinical characteristics of ALS patients who carry CCNF variants are largely unknown. Genetic analysis was performed for 1587 Chinese ALS patients, and missense variants were predicted by software analyses. Additionally, we searched PubMed, Embase, and Web of Science for relevant literature and conducted a meta-analysis of the frequency of variants. In our ALS cohort, we identified 29 nonsynonymous variants in 41 ALS patients. Among these ALS patients, 18 (1.1%) were carriers of 15 rare missense variants that were considered probably pathogenic variants, and 11 of 15 variants were novel. Seven relevant studies were identified, and a total of 43 CCNF variants in 59 ALS patients with a frequency of 0.8% were reported. The ratio of males to females in our cohort (10/8) was similar to that in Caucasian populations (4/7) and significantly higher than that in Asian populations (10/1). The proportion of bulbar onset in Caucasian CCNF carriers was similar to our cohort (25.0 vs. 27.8%); however, bulbar onset had never been reported in previous Asian studies (0/11). FTD was not found in CCNF carriers in previous Asian studies and our cohort, but it has been reported in a FALS cohort (1/75) of Caucasian individuals. There were some differences in the clinical characteristics among different ethnic ALS populations. More basic scientific studies are needed to elucidate the pathogenic mechanisms and genotype-phenotype associations of CCNF variants.

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Barbican-inspired bimetallic core–shell nanoparticles for fabricating natural leather-based radiation protective materials with enhanced X-ray shielding capability - Hao Li; Jibo Zhou; Linping Yan; Rui Zhong; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Catalytic performances of Cu-ZK-5 zeolites with different template agents in NH3-SCR - Yuchao Zang; Qing Li; Yalian Bi; Caixia Liu; Yan Zhang; Yanhua Wang; Min Zhang; Qingling Liu; Ziyin Zhang; Rui Han (Journal of Environmental Chemical Engineering, 2023)

Apatite and fluorite control the transport of tungsten in calcium-bearing hydrothermal fluids - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Zi-Qi Jiang; Lin-Bo Shang; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Mobile Phone Imaging Point Cloud Modelling for 3D Recording and Measurement of Small Scenes of Suspected Fossil Outcrops Found in the Field - Gao Sha; Gan Shu; Yuan Xiping; Hu Lin; Bi Rui; Li Raobo; Yang Ming (Geoheritage, 2023)

Alleviating effects of zinc and 24-epibrassionlide on cadmium accumulation in rice plants under nitrogen application - Zunxin Wang; Yang Li; Mingsong Liu; Ying Yang; Rui Wang; Siyuan Chen; Zongmei Liu; Feiyu Yan; Xinhong Chen; Junguo Bi; Zhiyao Dong; Feibing Wang (Chemosphere, 2023)

A systematic review of electrocoagulation technology applied for microplastics removal in aquatic environment - Fangyuan Liu; Chunpeng Zhang; Huilin Li; Nnanake-Abasi O. Offiong; Yuhang Bi; Rui Zhou; Hejun Ren (Chemical Engineering Journal, 2023)

Shape-controlled synthesis of Pd nanotetrahedrons with Pt-doped surfaces for highly efficient electrocatalytic oxygen reduction and formic acid oxidation - Liuxuan Luo; Zehao Tan; Cehuang Fu; Rui Xue; Xiaojing Cheng; Tianzi Bi; Lutian Zhao; Yangge Guo; Xiyang Cai; Jiewei Yin; Shuiyun Shen; Junliang Zhang (Chemical Engineering Journal, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Loss of Myomixer Results in Defective Myoblast Fusion, Impaired Muscle Growth, and Severe Myopathy in Zebrafish - Ping Wu; Pengzheng Yong; Zhanxiong Zhang; Rui Xu; Renjie Shang; Jun Shi; Jianshe Zhang; Pengpeng Bi; Elizabeth Chen; Shaojun Du (Marine Biotechnology, 2022)

Acetylsalicylic acid (ASA) suppressed Fusarium rot development and neosolaniol (NEO) accumulation by activating phenylpropane metabolism in muskmelon fruit - Lan Li; Qili Liu; Huali Xue; Yang Bi; Hussain Raza; Rui Zhang; Jimdjio Kouasseu Carelle; Hui Peng; Haitao Long; Dov Prusky (European Journal of Plant Pathology, 2022)

Two new cytotoxic cycloartane triterpenoids from Aphanamixis polystachya (Wall.) R. N. Parker - Yi-ting Wang; Shi-rui Fan; Jie-yun Cai; Jing-jing Guo; Xin-fang Zhang; Bi-juan Yang; Xiao-jiang Hao; Duo-zhi Chen (Natural Product Research, 2022)

A point cloud registration method based on dual quaternion description with point-linear feature constraints - Raobo Li; Xiping Yuan; Shu Gan; Rui Bi; Yan Guo; Sha Gao (International Journal of Remote Sensing, 2022)

Identification of epigenetic modifications mediating the antagonistic effect of selenium against cadmium-induced breast carcinogenesis - Zhuo-Zhi Liang; Yi-Xin Zhang; Rui-Mei Zhu; Yue-Lin Li; Hong-Mei Jiang; Ruo-Bi Li; Qian-Xin Chen; Qing Wang; Lu-Ying Tang; Ze-Fang Ren (Environmental Science and Pollution Research, 2022)

Analysis of geomorphologic features of the circular structure in the south of Lufeng Dinosaur Valley - Hu Lin; Gan Shu; Yuan Xiping; Yang MingLong; Gao Sha; Bi Rui; Li Yan (Earth Science Informatics, 2022)

Dimeric hexylitaconic acids from the marine-derived fungus Aspergillus welwitschiae CUGBMF180262 - Jiahui Han; Na Yang; Shangzhu Wei; Jia Jia; Rui Lin; Jiangpeng Li; Hongkai Bi; Fuhang Song; Xiuli Xu (Natural Product Research, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Synthesis, characterization and antitumor mechanism investigation of ruthenium(II) polypyridyl complexes with artesunate moiety - Bi-Chun Chen; Jun-Jian Lu; Ning Jiang; Xiu-Rong Ma; Rong-Tao Li; Rui-Rong Ye (JBIC Journal of Biological Inorganic Chemistry, 2021)

Local 3D scene fine detection analysis of circular landform on the southern edge of Dinosaur Valley - Gao Sha; Yuan Xiping; Gan Shu; Yang Milong; Hu Lin; Bi Rui (Arabian Journal of Geosciences, 2021)

Chlorogenic acid induces ROS-dependent apoptosis in Fusarium fujikuroi and decreases the postharvest rot of cherry tomato - Kai Kai; Rui Wang; Wanling Bi; Zhitao Ma; Wei Shi; Yingwang Ye; Danfeng Zhang (World Journal of Microbiology and Biotechnology, 2021)

Correction to: Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Photocatalytic purification of vehicle exhaust using CeO2–Bi2O3 loaded on white carbon and tourmaline - Yanqiu Bi; Rui Li; Fucheng Guo; Chundong Zhu; Jianzhong Pei (Environmental Science and Pollution Research, 2021)

New titanite U–Pb and molybdenite Re–Os ages for a hydrothermal vein-type Cu deposit in the Lanping Basin, Yunnan, SW China: constraints on regional metallogeny and implications for exploration - Juan Li; Lei-Luo Xu; Xian-Wu Bi; Yong-Yong Tang; Xiang-Yuan Sheng; Hai-Jun Yu; Gong Liu; Rui Ma (Mineralium Deposita, 2021)

Arbuscular mycorrhizal colonization rate of an exotic plant, Galinsoga quadriradiata, in mountain ranges changes with altitude - Gang Liu; Rui-Ling Liu; Wen-Gang Zhang; Ying-Bo Yang; Xiao-Qiong Bi; Ming-Zhu Li; Xiao-Yan Chen; Hua Nie; Zhi-Hong Zhu (Mycorrhiza, 2021)

Two new bioactive lignans from leaves and twigs of Cleistanthus concinnus Croizat - Shi-rui Fan; Jing-jing Guo; Yi-ting Wang; Bi-juan Yang; Duo-zhi Chen; Xiao-jiang Hao (Natural Product Research, 2020)

Two new norneolignans from Callicarpa kwangtungensis - Hong-Yu Bi; Chun-Liang Xu; Hui-Zheng Fu; Zhi-Qiang Zhou; Rui-Jian Zhong; Mian Dai; Dong Wang (Natural Product Research, 2020)

Physiological and Molecular Analysis of Sugarcane (Varieties—F134 and NCo310) During Sporisorium scitamineum Interaction - Pratiksha Singh; Qi-Qi Song; Rajesh Kumar Singh; Hai-Bi Li; Manoj Kumar Solanki; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2019)

The role of MAPK signaling pathway in formation of EMT in oral squamous carcinoma cells induced by TNF-α - Xiao-Wei Zhao; Jing-Ping Zhou; Yu-Lan Bi; Jia-Ying Wang; Rui Yu; Chao Deng; Wei-Kang Wang; Xian-Zhen Li; Rui Huang; Jili Zhang; De-Tao Tao (Molecular Biology Reports, 2019)

Flavonoid glucosides from the flowers of Trollius chinensis Bunge - Rui Yan; Yida Cui; Bowen Deng; Jiayi Bi; Guogang Zhang (Journal of Natural Medicines, 2019)

MiR-429 improved the hypoxia tolerance of human amniotic cells by targeting HIF-1α - Lihao Ge; Yuyan Wang; Yang Cao; Gang Li; Rui Sun; Peng Teng; Yansong Wang; Yunlong Bi; Zhanpeng Guo; Yajiang Yuan; Deshui Yu (Biotechnology Letters, 2018)

Direct and legacy effects of herbivory on growth and physiology of a clonal plant - Bi-Cheng Dong; Mo-Zhu Wang; Rui-Hua Liu; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Biological Invasions, 2018)

Biglycan, a Nitric Oxide-Downregulated Proteoglycan, Prevents Nitric Oxide-Induced Neuronal Cell Apoptosis via Targeting Erk1/2 and p38 Signaling Pathways - Sujuan Chen; Dandan Guo; Wei Zhang; Yunfei Xie; Haijie Yang; Binfeng Cheng; Lei Wang; Rui Yang; Jiajia Bi; Zhiwei Feng (Journal of Molecular Neuroscience, 2018)

Comparative growth increments of gladius surface and cross-sections to estimate Sthenoteuthis oualaniensis age - Xue Feng Wang; Bi Lin Liu; Jian Hua Li; Rui Jiang; Jing Yuan Lin; Teng Li (Marine Biology, 2018)

Cryobiotechnology of forest trees: recent advances and future prospects - Jing-Wei Li; Elif Aylin Ozudogru; Jiao Li; Min-Rui Wang; Wen-Lu Bi; Maurizio Lambardi; Qiao-Chun Wang (Biodiversity and Conservation, 2018)

The Arc Gene Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Rui Bi; Li-Li Kong; Min Xu; Guo-Dong Li; Deng-Feng Zhang; Tao Li; Yiru Fang; Chen Zhang; Buchang Zhang; Yong-Gang Yao (Molecular Neurobiology, 2018)

The complete mitochondrial genome of a threatened loach (Beaufortia kweichowensis) and its phylogeny - Zheng-Yong Wen; Bi-Wen Xie; Chuan-Jie Qin; Jun Wang; Deng-Yue Yuan; Rui Li; Yuan-Chao Zou (Conservation Genetics Resources, 2017)

NCAM affects directional lamellipodia formation of BMSCs via β1 integrin signal-mediated cofilin activity - Jia-Jia Bi; Jing Li; Bin-Feng Cheng; Hai-Jie Yang; Qiong-Qiong Ding; Rui-Fei Wang; Su-Juan Chen; Zhi-Wei Feng (Molecular and Cellular Biochemistry, 2017)

Identification and Efficiency of a Nitrogen-fixing Endophytic Actinobacterial Strain from Sugarcane - Zhen Wang; Manoj Kumar Solanki; Fei Pang; Rajesh Kumar Singh; Li-Tao Yang; Yang-Rui Li; Hai-Bi Li; Kai Zhu; Yong-Xiu Xing (Sugar Tech, 2017)

Rare Genetic Variants of the Transthyretin Gene Are Associated with Alzheimer’s Disease in Han Chinese - Qun Xiang; Rui Bi; Min Xu; Deng-Feng Zhang; Liwen Tan; Chen Zhang; Yiru Fang; Yong-Gang Yao (Molecular Neurobiology, 2017)

mtDNA Heteroplasmy in Monozygotic Twins Discordant for Schizophrenia - Hong Li; Rui Bi; Yu Fan; Yong Wu; Yanqing Tang; Zongchang Li; Ying He; Jun Zhou; Jinsong Tang; Xiaogang Chen; Yong-Gang Yao (Molecular Neurobiology, 2017)

The complete mitochondrial genome of a threatened loach (Sinibotia reevesae) and its phylogeny - Yuan-Chao Zou; Bi-Wen Xie; Chuan-Jie Qin; Yong-Ming Wang; Deng-Yue Yuan; Rui Li; Zheng-Yong Wen (Genes & Genomics, 2017)

The OPA1 Gene Mutations Are Frequent in Han Chinese Patients with Suspected Optic Neuropathy - A-Mei Zhang; Rui Bi; Qiu-Xiang Hu; Yu Fan; Qingjiong Zhang; Yong-Gang Yao (Molecular Neurobiology, 2017)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Effects of short-term inflammatory and/or hypoxic pretreatments on periodontal ligament stem cells: in vitro and in vivo studies - Yang Yu; Chun-Sheng Bi; Rui-Xin Wu; Yuan Yin; Xi-Yu Zhang; Ping-Heng Lan; Fa-Ming Chen (Cell and Tissue Research, 2016)

Neprilysin Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Hui-Zhen Wang; Rui Bi; Deng-Feng Zhang; Guo-Dong Li; Xiao-Hong Ma; Yiru Fang; Tao Li; Chen Zhang; Yong-Gang Yao (Molecular Neurobiology, 2016)

PLD3 in Alzheimer’s Disease: a Modest Effect as Revealed by Updated Association and Expression Analyses - Deng-Feng Zhang; Yu Fan; Dong Wang; Rui Bi; Chen Zhang; Yiru Fang; Yong-Gang Yao (Molecular Neurobiology, 2016)

Mitochondrial DNA Haplogroup A Decreases the Risk of Drug Addiction but Conversely Increases the Risk of HIV-1 Infection in Chinese Addicts - A-Mei Zhang; Qiu-Xiang Hu; Feng-Liang Liu; Rui Bi; Bi-Qing Yang; Wen Zhang; Hao Guo; Ian Logan; Yong-Tang Zheng; Yong-Gang Yao (Molecular Neurobiology, 2016)

Two new compounds from the roots of Ilex pubescens and their cytotoxic activity - Huan Xiong; Fang Zhao; Jiayi Bi; Yang Zhang; Guiyun Zhao; Xue Chen; Yuncong Li; Rui Yan; Qiang Zhao; Hua Qiao; Guogang Zhang (Journal of Natural Medicines, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Effects of light intensity and quality on phycobiliprotein accumulation in the cyanobacterium Nostoc sphaeroides Kützing - Rui Ma; Fan Lu; Yonghong Bi; Zhengyu Hu (Biotechnology Letters, 2015)

MTBP inhibits migration and metastasis of hepatocellular carcinoma - Qian Bi; Atul Ranjan; Rui Fan; Neeraj Agarwal; Danny R. Welch; Steven A. Weinman; Jie Ding; Tomoo Iwakuma (Clinical & Experimental Metastasis, 2015)

Cassiterite LA-MC-ICP-MS U/Pb and muscovite 40Ar/39Ar dating of tin deposits in the Tengchong-Lianghe tin district, NW Yunnan, China - Xiao-Cui Chen; Rui-Zhong Hu; Xian-Wu Bi; Hui-Min Li; Jiang-Bo Lan; Cheng-Hai Zhao; Jing-Jing Zhu (Mineralium Deposita, 2014)

Permeability Comparison between Hepatocyte and Low Efflux MDCKII Cell Monolayer - Rui Li; Yi-An Bi; Yurong Lai; Kiyohiko Sugano; Stefanus J. Steyn; Patrick E. Trapa; Li Di (The AAPS Journal, 2014)

Magma mixing revealed from in situ zircon U–Pb–Hf isotope analysis of the Muhuguan granitoid pluton, eastern Qinling Orogen, China: implications for late Mesozoic tectonic evolution - Rui Liu; Jian-Wei Li; Shi-Jian Bi; Hao Hu; Mi Chen (International Journal of Earth Sciences, 2013)

Molybdenite Re–Os and muscovite 40Ar/39Ar dating of quartz vein-type W–Sn polymetallic deposits in Northern Guangdong, South China - Hua-Wen Qi; Rui-Zhong Hu; Xiao-Fei Wang; Wen-Jun Qu; Xian-Wu Bi; Jian-Tang Peng (Mineralium Deposita, 2012)

Mantle-derived noble gases in ore-forming fluids of the granite-related Yaogangxian tungsten deposit, Southeastern China - Rui-Zhong Hu; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Jian-Tang Peng; You-Qiang Qi; Li-Yan Wu; Wen-Feng Wei (Mineralium Deposita, 2012)

Effects of Danggui Buxue Tang, a traditional Chinese herbal decoction, on high glucose-induced proliferation and expression of extracellular matrix proteins in glomerular mesangial cells - Hao-Liang Ke; Ying-Wen Zhang; Bi-Fa Zhou; Rui-Tang Zhen (Natural Product Research, 2012)

The Influence of Landscape Features on Road Development in a Loess Region, China - Xiaoli Bi; Hui Wang; Rui Zhou (Environmental Management, 2011)

Foot-and-mouth disease virus leader proteinase inhibits dsRNA-induced RANTES transcription in PK-15 cells - Dang Wang; Liurong Fang; Jing Bi; Quangang Chen; Lu Cao; Rui Luo; Huanchun Chen; Shaobo Xiao (Virus Genes, 2011)

He and Ar isotopic compositions and genetic implications for the giant Shizhuyuan W–Sn–Bi–Mo deposit, Hunan Province, South China - Li-Yan Wu; Rui-Zhong Hu; Jian-Tang Peng; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Qiao-Yun Wang; Ya-Ying Liu (International Geology Review, 2011)

A study of perfectly matched layers for joint multicomponent reverse-time migration - Qi-Zhen Du; Rui-Yan Sun; Tong Qin; Yi-Tong Zhu; Li-Fei Bi (Applied Geophysics, 2010)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

Identification of low abundance polyA-binding proteins in Arabidopsis chloroplast using polyA-affinity column - Rui-Juan Ni; Zhuo Shen; Chuan-Ping Yang; Ya-Dan Wu; Ying-Dong Bi; Bai-Chen Wang (Molecular Biology Reports, 2010)

Transcriptional responses of Haemophilus parasuis to iron-restriction stress in vitro - Qiyun Xie; Hui Jin; Rui Luo; Yun Wan; Jie Chu; Hufeng Zhou; Bi Shi; Huanchun Chen; Rui Zhou (BioMetals, 2009)

A novel drought-inducible gene, ATAF1, encodes a NAC family protein that negatively regulates the expression of stress-responsive genes in Arabidopsis - Ping-Li Lu; Nai-Zhi Chen; Rui An; Zhao Su; Bi-Shu Qi; Fei Ren; Jia Chen; Xue-Chen Wang (Plant Molecular Biology, 2006)

Production and analysis of transgenic wheat (Triticum aestivum L.) with improved insect resistance by the introduction of cowpea trypsin inhibitor gene - Rui-Ming Bi; Hai-Yan Jia; De-Shun Feng; Hong-Gang Wang (Euphytica, 2006)

Geology and geochemistry of Carlin-type gold deposits in China - Hu Rui-Zhong; Su Wen-Chao; Bi Xian-Wu; Tu Guang-Zhi; Albert Hofstra (Mineralium Deposita, 2002)